Pengelolaan Sampah Untuk Menunjang Smart Environment Sebagai Unsur Smart City - Aprilina, Femila; Rochana, Erna; Raidar, Usman (CV Insan Kreasi Media, 2025)
The rapid urbanization in Bandar Lampung City has led to a significant increase in waste volume, reaching 850 tons per day, driven by population growth, air pollution, and limited green spaces. This situation poses serious environmental challenges, including pollution and health risks, making effective waste management crucial for supporting the Smart Environment concept as part of Smart City initiatives that integrate technology for sustainable urban development. The urgency of this topic lies in the need to address unsustainable waste practices that threaten ecological balance and quality of life, while its significance is evident in contributing to global sustainability goals and enhancing urban resilience. This study aims to analyze factors increasing waste volume, challenges in sustainable waste management implementation, and government policies supporting Smart Environment. The research employs a descriptive qualitative approach. Data collection involved in-depth interviews with key informants from the Environmental Agency, field observations, and document analysis. Data analysis followed Miles and Huberman's model, including data reduction, display, and conclusion drawing, with triangulation for validity. Findings reveal that waste volume increases due to population growth, low public awareness of 3R practices, inadequate infrastructure like overcapacity landfills, and impulsive consumption patterns. Implementation challenges include low community participation, insufficient infrastructure, and funding issues. Government policies, such as Sanitary Landfills, Waste-to-Energy Plants (PLTS), and Waste Banks, support Smart Environment dimensions like resource management and sustainable urban planning. The study recommends infrastructure investment, continuous education, and cross-sector collaboration for environmental sustainability in the Smart City context.